KOMPETENSI MAHASISWA PRAKTEK PENGALAMAN LAPANGAN 2 PROGRAM STUDI PENDIDIKAN JASMANI TAHUN 2018 DI KOTA PONTIANAK - Khairuddin, Khairuddin; Triansyah, Andika; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was conducted to determine the competency of the student's Field Experience Practice (PPL) Physical Education Study Program at Tanjungpura University during the guidance process in the Field Experience Practice (PPL) conducted. This research can be used to improve the quality of preparation for prospective physical education teachers and the satisfaction and trust of physical education teachers and schools to receive PPL students of Physical Education study programs at Tanjungpura University. Moreover, it will be seen the quality of the preparation of prospective educators, namely sports teachers who meet the competencies that they must have. The survey research method is a quantitative study using the same structured or systematic questions to many people, for then all answers obtained by researchers are recorded, processed and analyzed, the Competency of Student Practice Field Experience Physical Education Study Program 2018 in Pontianak achieved an actual score of 6303 from an ideal score of 8064 meaning it reached 78.16% of what it should be, thus belonging to the "Very Good" category. Keywords: Competence of Student Practice Field Experience Educational Study Programs